1996
DOI: 10.1097/00007691-199610000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Gentamicin Therapy in Preterm Neonates Includes Loading Doses and Early Monitoring

Abstract: Recent studies have suggested the inadequacy of an initial gentamicin 2.5 mg/kg standard dose in neonates and the need for a loading dose. The purpose of this prospective, randomized study was to compare initial peak and initial trough serum gentamicin concentrations (SGC) in neonates after a standard dose (2.5 mg/kg) or a loading dose (4 mg/kg) on the first day of life. A secondary objective of the study was to evaluate the use of two SGC drawn after the first dose in designing individualized dosage regimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Some authors suggested using a loading dose of 4-5 mg/ kg to shorten the time between the first dose of gentamicin and the time when gentamicin therapeutic serum concentration is reached [26][27][28][29]. The introduction of once-daily Loading dose of 5 mg/kg followed by a maintenance dose of 3.5 mg/kg f Loading dose of netilmicin of 5 mg/kg followed by maintenance dose of 5 mg/kg (body weight 2,000-2,500 g), 4 mg/kg (body weight 1,500-2,000 g), 3 mg/kg (body weight 1,000-1,500 g), 1.5 mg/kg (body weight 1,000-1,500 g) and 1 mg/kg (body weight <1,000 g) dosing and the extended interval between dose regimens, which require 4-5 mg/kg of gentamicin, makes the use of the loading dose unnecessary.…”
Section: Gentamicinmentioning
confidence: 99%
“…Some authors suggested using a loading dose of 4-5 mg/ kg to shorten the time between the first dose of gentamicin and the time when gentamicin therapeutic serum concentration is reached [26][27][28][29]. The introduction of once-daily Loading dose of 5 mg/kg followed by a maintenance dose of 3.5 mg/kg f Loading dose of netilmicin of 5 mg/kg followed by maintenance dose of 5 mg/kg (body weight 2,000-2,500 g), 4 mg/kg (body weight 1,500-2,000 g), 3 mg/kg (body weight 1,000-1,500 g), 1.5 mg/kg (body weight 1,000-1,500 g) and 1 mg/kg (body weight <1,000 g) dosing and the extended interval between dose regimens, which require 4-5 mg/kg of gentamicin, makes the use of the loading dose unnecessary.…”
Section: Gentamicinmentioning
confidence: 99%
“…[2][3][4] Protocols for initial gentamicin dosage regimens in neonates are often complex, as they incorporate multiple variables such as birth weight, gestational age at birth, postnatal age, and other ontogenic qualities and clinical risk factors. [5][6][7][8][9][10][11][12][13][14][15] Of these, birth weight is strongly correlated with gestational age at birth, and it remains a more consistent, sensitive, and precise predictor of gentamicin clearance in neonates than does gestational age at birth, postnatal age, or serum creatinine concentration (S cr ), making birth weight an attractive and easily retrievable choice for use in a neonatal gentamicin dosing protocol. 4,16 Simplified protocols are also less prone to dosing error than are more complex protocols.…”
mentioning
confidence: 99%
“…Early studies suggest dose adjustment on the basis of both gestation and postnatal age, [15][16][17][18] and use of a ''loading dose'' is recommended. 19 Extrapolation of the results of detailed, developed country pharmacokinetic studies to resource poor settings may also be difficult. In one study where it is explicitly reported, almost 20% of infants had dose adjustments made during a study of once daily treatment as a result of drug concentration results.…”
mentioning
confidence: 99%